A RELEVÂNCIA DE INSTIGAR UM DEBATE NA INSTITUIÇÃO PÚBLICA EDUCACIONAL: IGUALDADE DE GÊNERO X DIREITOS HUMANOS (Interdisciplinary Studies Journal, 2024)
Abstract: This article deals with providing opportunities for teaching, students and the local community with the opportunity to dialogue about the importance of the role that women paper in the family, at work, in society and in social, governmental or non-governmental organizations. Whose objective of study is to promote equal rights between women and men. In order to value it while respecting its gender. In order to value it while respecting its gender. Regarding the methodology, it will be through exploratory research, bibliographic and documentary. It is justified, therefore, from the constitutional premise that all people have guaranteed and legitimized rights of equality, according to the Federal Constitution of 1988, which legitimizes in Article 5. Thus, it is a very important theme to be instigated in Schools, Federal Institutes and Public Universities. It can be debated from the Initial or Final Years of Elementary School. According to the age group of the students, the topic should be addressed. In addition, it can be discussed in High School, Technical Education or Undergraduate Courses. Because it is from these dialogues that the results can be obtained. The target audience reached will be able to reflect on the theme. And disseminate it in the family, in social groups, at work etc. Keywords: Education; Gender; Human Rights; Institutions.